1996
DOI: 10.1111/j.1432-1033.1996.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Propeptide‐Assisted Folding of the Calcium‐Dependent Protease of the Cyanobacterium Anabaena

Abstract: The Ca"-dependent protease of the cyanobacterium Anabuena vuriabilis is a cytoplasmic enzyme with a substrate specificity like trypsin. Its previously published DNA sequence [Maldener, I., Lockau,Genet. 225, 113-1201 contained a sequencing error. Here we report the corrected sequence which shows, that the Ca2+-protease belongs to the family of subtilases (subtilisin-like serine proteases). Consistent with its cytoplasmic localization, a pre-sequence is not found.The enzyme is produced as a precursor with a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Although HreP shows the highest similarity to PrcA of A. variabilis, PrcA is autocatalytically processed after an Arg residue, in contrast to processing after Lys by HreP. Furthermore, the PrcA cleavage site does not appear to have a consensus sequence (R-E-F-R-Q-R*) typical for subtilisin/kexinlike proteases (5). This suggests that HreP and PrcA cleave different substrates and may also have different functions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although HreP shows the highest similarity to PrcA of A. variabilis, PrcA is autocatalytically processed after an Arg residue, in contrast to processing after Lys by HreP. Furthermore, the PrcA cleavage site does not appear to have a consensus sequence (R-E-F-R-Q-R*) typical for subtilisin/kexinlike proteases (5). This suggests that HreP and PrcA cleave different substrates and may also have different functions.…”
Section: Discussionmentioning
confidence: 93%
“…Only one prokaryotic protease, PrcA of A. variabilis, showed significant similarity. Both HreP and PrcA share typically conserved residues that have been identified by sequence alignments and by a comparison of the crystal structures of several subtilases (5,32,46). One of three residues that are specific for the kexin subfamily of subtilases is conserved in HreP as well as in PrcA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mature domains alone are not folded into an active form but are folded into an inactive form with molten-globular structure in the absence of propeptides (15,44). The requirement for a propeptide for maturation of its cognate mature domain has also been reported, not only for other members of the subtilase family (5,7,34), but also for other proteases (33,38,39,49,51,62). However, it remains to be determined whether archaeal subtilisins mature in a similar manner.…”
mentioning
confidence: 99%
“…Moreover, a calcium-dependent trypsin-like peptidase, a calcium-independent peptidase and a prolyl endopeptidase extracted from the cultures of Anabaena variabilis ATCC 29413 (A. variabilis 29413) have been shown to carry out proteolytic degradation of a number of natural and synthetic peptidase substrates (Lockau et al 1988;Strohmeier et al 1994;Maldener et al 1991), which suggests that extensive proteolytic activity inside the cells of heterocytous cyanobacteria does occur. A calcium-dependent peptidase from A. variabilis 29413 (Lockau et al 1988) which was also found in Anabaena 7120 was later characterized to be a subtilisin-like serine peptidase, PrcA, Ava_4009 (Baier et al 1996). With the advent of a full genome sequence of Anabaena sp.…”
Section: Introductionmentioning
confidence: 99%